SEARCHING FOR CFC’s AND HCFC’s ALTERNATIVES. Part I: A REFRIGERANT DESIGN STRATEGY USING GROUP CONTRIBUTION METHODS (Sciences & Technology. A, exactes sciences, 2000)
It is now well established that the chlorofluorocarbons (CFC’s), the hydrochlorofluorocarbons (HCFC’s) and other chlororinated hydrocarbons which are compounds mostly used as refrigerants, are causing more damages than benefits to the environment and particularly to the ozone layer. Therefore one can see how important it is to search for substitutes to these compounds with desirable combination of physical properties to meet the needs of specific applications but, ultimately, with no harms to the environment.In this paper, although the bases of a computer-aided design of refrigerants (CADR) method being developed are outlined, the main purpose still remains the demonstration of the great ability and importance of group contribution methods in the development of such techniques, particularly for predicting vapour-liquid equilibria and other thermodynamic properties like the enthalpy or entropy of generated systems, by the use of models like the UNIFAC.